2019
DOI: 10.1186/s12943-019-1072-5
|View full text |Cite
|
Sign up to set email alerts
|

Circ-AKT3 inhibits clear cell renal cell carcinoma metastasis via altering miR-296-3p/E-cadherin signals

Abstract: BackgroundCircular RNA (circRNA) is a type of circular endogenous RNA produced by special selective splicing and participates in progression of diverse diseases. However, the role of circRNA in clear cell renal cell carcinoma (ccRCC) is still rarely reported.MethodsWe detected lower circ-AKT3 expression in ccRCC using the circular RNA microarray. Then, qPCR array was applied to verify the expression of circ-AKT3 in between 60 ccRCC tissues and adjacent normal tissues, as well as ccRCC cell lines and human norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 47 publications
2
114
0
Order By: Relevance
“…Before the present study, various studies demonstrated that miRNAs such as hsa-miR-137 [54,55], hsa-mir-211-5p [56], hsa-mir-224-5p [57], hsa-miR-335-5p [58], and hsa-mir-296-3p [59], are involved in the regulation of RCC progression. In addition, increased hsa-miRNA-9 and decreased hsa-miRNA-200a could serve as biomarkers for distinguishing hemangioblastomas from metastatic clear cell RCC [60].…”
Section: Discussionmentioning
confidence: 65%
“…Before the present study, various studies demonstrated that miRNAs such as hsa-miR-137 [54,55], hsa-mir-211-5p [56], hsa-mir-224-5p [57], hsa-miR-335-5p [58], and hsa-mir-296-3p [59], are involved in the regulation of RCC progression. In addition, increased hsa-miRNA-9 and decreased hsa-miRNA-200a could serve as biomarkers for distinguishing hemangioblastomas from metastatic clear cell RCC [60].…”
Section: Discussionmentioning
confidence: 65%
“…We [27]. Differentially, circ-AKT3 overexpression was demonstrated to decrease migrated and invaded CCRCC cells [28]. CircRNA cRAPGEF5 [29] and has_circ_0072309 [30] also impeded tumor growth and metastasis in CCRCC.…”
Section: Discussionmentioning
confidence: 91%
“…Increasing data have shown that a variety of organisms could generate circRNAs by back-splicing, including Drosophila [25], rice [26], silkworm [27], zebrafish [28], and humans [29]. In addition to cellular transcripts, viral transcripts were found to form circRNAs in KSHV-infected primary effusion lymphoma cells, EBV-infected cells [20,21] or HPV16 [23].…”
Section: Discussionmentioning
confidence: 99%